RI sensing system with high sensitivity and large measurement range using a microfiber MZI and a photonic crystal fiber MZI. (May 2020) - Xia, Feng; Zhao, Yong
Highlights: Ultra-sensitive RI measurement in large range is realized by an optical fiber sensing system. An ultra-high sensitivity of 44271 nm/RIU is achieved by the microfiber MZI with DTP. Measurement range of the microfiber MZI is expanded by using a SMF-PCF-SMF MZI. The sensing scheme solves the trade-off between high sensitivity and large measurement range. Abstract: A dual-channel optical fiber sensing system for refractive index (RI) measurement with ultra-high sensitivity and large measurement range is proposed and demonstrated by combining a rough measurement sensor and a precise measurement sensor. One sensing channel consists of an optical microfiber Mach-Zehnder interferometer (MZI), which works as a RI precise measurement sensor. The microfiber MZI is fabricated on a single mode fiber (SMF) by using a two-step tapering method. The microfiber MZI operating around dispersion turning point (DTP) shows an ultra-high sensitivity of up to 44271 nm/RIU, however, its measurement range is limited to be only 0.0015 owing to the periodic interference spectrum. The other sensing channel contains an SMF-photonic crystal fiber (PCF)-SMF MZI, which works as a RI rough measurement sensor. RI sensitivity of the SMF-PCF-SMF MZI is 143.67 nm/RIU in 1.3317–1.3710. RI measurement range of the microfiber MZI is expanded by firstly read a rough RI value from the SMF-PCF-SMF MZI and then determine the observation window of the interference spectrum of the microfiber MZI. This proposed sensing scheme solves the trade-off between high sensitivity and large measurement range caused by the periodic interference spectrum, and it is promising in liquid RI-related sensing fields with high requirements of both sensitivity and measurement range.